Attitudes toward hiring and working with homosexuals in Southern California law enforcement agencies - Doyle, James Frederick (1995)
The purpose of this research is to examine the acceptability of male homosexuals in law enforcement as determined by those currently employed as sworn officers in Southern California. Law enforcement has historically been reluctant to accept outsiders within its ranks. It has only been within the last 25 years that women and minorities have sought to enter the law enforcement profession in significant numbers, and it took legislative action and law suits to make this a reality